Vegetative Growth Response Of North Halmahera Local Rice To Inundation - Christin Jilia Rosalia Kakanga; Jeany Sh Polii- Mandang; Edy F. Lengkong; Jeanne Martje Paulus (Jurnal Agroekoteknologi Terapan, 2022)
Research on the Vegetative Growth Response of Halut Local Rice to inundation has been carried out. This study aims to examine the morphological response of local rice plants in North Halmahera to flooding during the growth phase.This research was carried out using polybags in the greenhouse of the Agriculture Service of North Halmahera Regency using a completely randomized basic design experiment consisting of 2 factors, the first factor was variety and the second factor was the provision of inundation stress. Data were analyzed by analysis of variance (ANOVA). The characters observed in this study included plant height, number of leaves, root length, and speed of stem elongation.The results showed that the treatment factors had significant differences when experiencing 10 days of inundation stress which was found in the observation character of the number of leaves. Meanwhile, the treatment factor, the variety factor, and the interaction between the treatment factor and the variety showed a very significant difference when experiencing a 20-day inundation on the observation of the number of leaves. The character of plant height, root length, and speed of stem elongation showed no significant effect on treatment factors, varietal factors, and interactions between treatment factors and varieties.The morphological response of Halut rice varieties to flooding was that only the number of leaves was significantly influenced by flooding factors compared to other parameters (plant height, root length, and stem elongation speed). Based on the agronomic character of the number of leaves, the singing variety is more resistant/tolerant to flooding.Keywords: Inundation, Morphological Response, North Halmahera Local Rice